(untitled) (International journal of artificial intelligence, 2024)
This research aims to investigate the relationship between customer loyalty programs and customer retention in Uzbekistan. Even though the competition is growing in Uzbek business market, loyalty programs are still not very popular. This research, which targeted 82 participants, aims at finding out whether loyalty programs influence the level of customer loyalty and result repeat purchases. The evidence shows that loyalty programs actually do play a role in the choice of brand, customer loyalty and spending behavior. Also, it is equally important to have emotional involvement of customers by offering discounts and point based rewards. From the research findings it can be concluded that businesses operating in Uzbekistan could greatly benefit if they design good loyalty programs.